Dagger magic : a novel of the Adept - Kurtz, Katherine; Harris, Deborah Turner (New York : Ace Books, 1996)
Adam Sinclair faces mankind's most dire threat--a cult older than Christianity with the power to resurrect a new, demonic Third Reich.
Keywords: Nazis -- Fiction; Fantasy fiction